2011
DOI: 10.1186/0778-7367-69-9
|View full text |Cite
|
Sign up to set email alerts
|

How can the results of a qualitative process evaluation be applied in management, improvement and modification of a preventive community trial? The IHHP Study

Abstract: BackgroundThis study reports the results of the qualitative process evaluation (PE) of the Isfahan Healthy Heart Program (IHHP), an integrated community-based trial for prevention and control of non-communicable diseases in Iran.MethodsThe study explored the overall quality of program implementation. The participants, including designers of IHHP, stakeholders and community members (n = 60) were purposefully recruited from the intervention areas. Data collected from semi-structured interviews and field notes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…Cardiovascular disease (CVD) is a common disorder worldwide, accounting for 31% of all global deaths (World Health Organization, ), and is one of the leading causes of death, both in developed and developing countries (Pagidipati & Gaziano, ; Sarrafzadegan, Rabiei, Alavi, Abedi, & Zarfeshani, ). Cardiac rehabilitation (CR) is a valuable and cost‐effective secondary prevention strategy, which has been identified as an essential part of contemporary health care for patients with CVD (Alavi, Irajpour, Giles, Rabiei, & Sarrafzadegan, ).…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular disease (CVD) is a common disorder worldwide, accounting for 31% of all global deaths (World Health Organization, ), and is one of the leading causes of death, both in developed and developing countries (Pagidipati & Gaziano, ; Sarrafzadegan, Rabiei, Alavi, Abedi, & Zarfeshani, ). Cardiac rehabilitation (CR) is a valuable and cost‐effective secondary prevention strategy, which has been identified as an essential part of contemporary health care for patients with CVD (Alavi, Irajpour, Giles, Rabiei, & Sarrafzadegan, ).…”
Section: Introductionmentioning
confidence: 99%
“…The important role of macro-level support has also been emphasized by Lee et al [23] who in their qualitative study reported that existing systems, structures, and policies could not support the implementation of the guideline and are actually important obstacles to its implementation. Another policy-related issue highlighted in other studies is resource allocation [24,25]. Particularly, a reduction in human resources" capacity can result in excessive pressure on physicians and other health team members [26].…”
Section: Discussionmentioning
confidence: 99%
“…Implementing evidence based programmes could reduce negative perceptions about health programmes and policies while increasing adoption and compliance [ 64 ]. While, evidence based public health is more nuanced and in the past decade has tried to develop and evaluate standards based on research of preventative health programmes and services, to determine which types of prevention programmes are more successful and the translation of such programmes across populations [ 65 ].…”
Section: Introductionmentioning
confidence: 99%